EXPLANATION OF THE MOLECULAR MECHANISM OF ANTI-DEPRESSION THERAPY USING WEBINARS AS LEARNING COMMUNICATION MEDIA - Adhe Septa Ryant Agus; Junaidi Khotib (Universitas Airlangga, 2023)
The Covid-19 Pandemic outbreak has changed various forms of life in society, including restrictions on activities in an open-source environment. The pandemic has also created various kinds of unresolved mental health problems, both in the national dan global area, both those who are directly exposed to the virus and those who are not. Today, the community is still struggling to control the spread of Covid-19, but on the other hand, it has caused the spread of feelings of anxiety, fear and mental pressure due to isolation, physical distancing restrictions, social relations, and other uncertainties. Therefore, these webinar activities were held as one of the online learning communication media, in terms of providing mattery regarding the molecular mechanism of antidepressant therapy, which during the post-Covid-19 pandemic its use increased due to social reasons. This webinar media was very effective without having to gather a crowd and aims to increase knowledge, especially among participants in terms of handling mental health such as depression in terms of its pharmacology therapy. Then, knowing the mechanism of molecular action can improve the optimization of antidepressant therapy according to the patient’s condition. The target participants in this webinar are health workers, students of health study programs, and common people. The webinar activity was conducted by the online system, using the Zoom meeting platform, and was held on April 15th, 2023, then was attended by 241 people, who came from all over Indonesia. From the implementation of the webinar activities, it is known that there has been an increase in understanding of the molecular matter that has been given, this can be seen from the percentage of the correct answers in the post-test evaluation compared to the answers in the pre-test.